Comparative Effectiveness of Oxaliplatin Versus 5-flourouricil in Older Adults. Issue 5 (September 2015) - Mack, Christina DeFilippo; Brookhart, M. Alan; Glynn, Robert J.; Meyer, Anne Marie; Carpenter, William R.; Sandler, Robert S.; Stürmer, Til
<x xml:space="preserve">Abstract</x> Background: Oxaliplatin was rapidly adopted for treatment of stage III colon cancer after FDA approval in November 2004, thus providing an opportunity to use calendar time as an instrumental variable in nonexperimental comparative effectiveness research. Assuming instrument validity, instrumental variable analyses account for unmeasured confounding and are particularly valuable in sub-populations of unresolved effectiveness, such as older individuals. Methods: We examined stage III colon cancer patients ages 65+ years initiating chemotherapy between 2003 and 2008 using US population-based cancer registry data linked with Medicare claims (N = 3, 660). Risk differences for all-cause mortality were derived from Kaplan–Meier survival curves. We examined instrumental variable strength and compared risk differences with propensity score estimates. Results: Calendar time greatly affected oxaliplatin receipt. The calendar time instrument compared patients treated from January 2003 through September 2004 (N = 1, 449) with those treated from March 2005 through May 2007 (N = 1, 432), resulting in 54% compliance. The 1-, 2-, and 3-year local average treatment effect of the risk differences per 100 patients in the "compliers" (95% confidence intervals) were −4.6 (−8.2, −0.44), −6.3 (−12, −0.16), and −9.2 (−15, −2.5), respectively. Corresponding propensity score-matched results were −1.9 (−4.0, 0.2), −3.4 (−6.2, −0.05), and −4.3 (−7.5, −0.96). Conclusions: Instrumental variable and propensity score analyses both indicate better survival among patients treated with oxaliplatin. As these results are based on different populations and assumptions, the instrumental variable analysis adds to evidence of oxaliplatin's effectiveness in older adults, who bear the greatest burden of colon cancer yet were underrepresented in clinical trials. In nonexperimental comparative effectiveness research of rapidly emerging therapies, the potential to use calendar time as an instrumental variable is worth consideration.